2013
DOI: 10.1097/cej.0b013e32835b385d
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of fluvastatin in rat mammary carcinogenesis

Abstract: On the basis of preclinical and clinical evidence, statins lead to risk reduction of several types of neoplasia including breast cancer. This study is the first report on the preventive effects of fluvastatin in experimental breast cancer in vivo. In this experiment, the antineoplastic effects of fluvastatin in the chemoprevention of N-methyl-N-nitrosourea-induced mammary carcinogenesis in female rats were evaluated. The effects of fluvastatin on selected parameters of apoptosis, proliferation, and angiogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Murine models of breast cancer when treated with statins were found to undergo increased apoptosis as well as decreased tumor cell proliferation. [10][11][12] Statins also reduced the proliferation of cancer cells in murine models of colon, liver, pancreatic, ovarian, and prostate cancers. [13][14][15][16] Epidemiologic studies have shown an inverse association of statin use with the incidence of uterine and ovarian cancer.…”
mentioning
confidence: 99%
“…Murine models of breast cancer when treated with statins were found to undergo increased apoptosis as well as decreased tumor cell proliferation. [10][11][12] Statins also reduced the proliferation of cancer cells in murine models of colon, liver, pancreatic, ovarian, and prostate cancers. [13][14][15][16] Epidemiologic studies have shown an inverse association of statin use with the incidence of uterine and ovarian cancer.…”
mentioning
confidence: 99%
“…In our previous study, highly effective treatment of rat mammary carcinomas by fluvastatin caused only slight increase in caspase‐3 expression (Kubatka et al . ). In this experiment, the apoptosis execution proteins caspase‐3 and caspase‐7 were significantly increased by pravastatin in tumour cells; moreover, with pravastatin+melatonin combination, this effect on both caspases noticeably enhanced.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, significant anti‐tumour effects of dietary administered lipophilic statins (atorvastatin, simvastatin and fluvastatin) in the chemoprevention of rat mammary carcinogenesis in our previous studies were observed (Kubatka et al . , , ). In our recent experiment, hydrophilic rosuvastatin (250 mg/kg) has shown lower non‐significant anti‐neoplastic activity than lipophilic statins in this model of experimental breast cancer (Kubatka et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations